2014
DOI: 10.1108/srj-04-2012-0086
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility: towards a context-specific perspective in developing countries

Abstract: Purpose – This paper aims to empirically test, in the Niger Delta region of Nigeria, the external perceptions which hold that a firm that has acted in a socially irresponsible manner can have negative consequences, as an organisation’s success and very survival depends, in part, on satisfying normative expectations from its environment. Design/methodology/approach – A purposive sample of 28 respondents was selected from three communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…This is mostly because in developing countries research on CSR is still neither mainstreamed nor found relevant [91]. However, the numerous positive effects of CSR on companies in developed countries, especially improvement of financial performance and attraction and engagement of employees [92] have influenced companies/organizations in developing countries to follow their footsteps [93,94], which is of great importance for the Western Balkan countries in which more and more business organizations introduce the practice of CSR [47,[95][96][97][98][99][100][101][102][103]. Studies pertaining to CSR in the Western Balkan countries are mainly descriptive or qualitative.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mostly because in developing countries research on CSR is still neither mainstreamed nor found relevant [91]. However, the numerous positive effects of CSR on companies in developed countries, especially improvement of financial performance and attraction and engagement of employees [92] have influenced companies/organizations in developing countries to follow their footsteps [93,94], which is of great importance for the Western Balkan countries in which more and more business organizations introduce the practice of CSR [47,[95][96][97][98][99][100][101][102][103]. Studies pertaining to CSR in the Western Balkan countries are mainly descriptive or qualitative.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, considering the fact that in most of the cases the implementation of CSR standards is voluntary, the development of CSR practices and initiatives is still not at satisfactory level, despite the existence of legislation and a number of undertaken activities regarding the concept of CSR [47,90,[95][96][97][98][99][100][101][102][103]. In other words, although there are significant government initiatives in the analyzed countries, as well as adopted policies and strategies, the issue of social responsibility is still perceived as declaratory, i.e., voluntary, rather than obligatory, i.e., imperative [90,94]. So, the employees' attitudes and perceptions were recognized as one of the potentially important factors for future development and implementation of this concept.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The implications of this view are, first, corporate profitability is a necessary condition of social responsibility (Scott, 2007). Second, companies should more closely consider local issues when drawing up CSR policy guidelines in a non-Western environment (Ozuem et al, 2014). Third, conceptual framework for the corporate citizenship notion implies business and political perspective of corporate citizenship (Camilleri, 2017).…”
Section: Corporate Social Responsibility (Csr)mentioning
confidence: 99%
“…Ignoring CSR and indulging in socially irresponsible behavior (e.g., pollution, faulty or dangerous products resulting into consumer injuries, worker accidents due to poor safety conditions) can have dire consequences (Campbell, 2007). At the same time, socially responsible investments enhance cohesion between corporate and communities (Ozuem et al, 2014). By using carefully crafted social strategies, firms take actions to maintain the complex relationships with shareholders, employees, clients and the community (Husted & Allen, 2007).…”
Section: Introductionmentioning
confidence: 99%